(untitled) (CIPEEX, 2025)
The analysis of the presence of hypertension and diabetes and falls in the elderly seeks to determine a relationship between these variables, aiming to develop and advance prevention and awareness mechanisms regarding this problem that persists in the lives of the elderly. The objective of this study was to determine the prevalence of falls among community-dwelling elderly individuals who have hypertension and diabetes mellitus. The study consists of a data snapshot, in a descriptive and quantitative cross-sectional manner, where economic and sociodemographic aspects, general health, level of frailty, and functional autonomy of the elderly were evaluated. Elderly individuals aged 60 or older, with hypertension and diabetes mellitus, were included in the study. The sample consisted of one hundred and ten elderly individuals (n = 110) who met the inclusion criteria and agreed to participate. It was found that 38.2% (n=42) of the elderly with hypertension and diabetes mellitus had falls in the last twelve months, and 21.8% (n=24) reported having had only one fall in the last twelve months. The results also indicate that 36.84% of the elderly with diabetes mellitus and 50% of the elderly with hypertension reported having fallen in the last 12 months, demonstrating a considerable prevalence of these occurrences in this group. Although preventive actions have reduced the number of falls, it is important to continue focusing on strategies to further decrease this prevalence and improve the quality of life for the elderly.